Megjegyzések az aracsi középkori templom történeti és régészeti kutatásához - Berta Adrián (Középkortörténeti tanulmányok, 2015)
The medieval town Aracs and the ruins of a Franciscan church were located in the middle region of the former Torontói county, 12 km northeast from Törökbecse. The lack of written sources has caused problems in connection with the early history of the settlement and the ecclesiastical institution. The exact date of the church foundation is unknown, but considering the style of the building it can be argued that it was built during the first half of the 13th century. The town was mentioned in 1332 for first time among the village parishes of this region. The Franciscan church and monastery was mentioned twice during the last quarter of the 14th century. The medieval town was destroyed during the Ottoman period. The archaeological investigations of the site started in the second half of the 19th century. In the last hundred years, there have been numerous archaeological excavations in the surroundings of the medieval ruins. Up to the present the territory inside the church, most part of the monastery and a smaller part of the medieval cemetery has been excavated. Yet, the archaeological results and interpretations of the site are questionable because of the fractional and imperfectly documented excavation data. The existence of the subsequently identified previous parish church is uncertain as well. The next step of the further research should be the systematic gathering of historical sources and archaeological data concerning the medieval site.